Current Condition of Vessels on Inland Waterways in Croatia - Jurum-Kipke, Jasna; Maković, Branko; Sumpor, Davor (Promet - Traffic&Transportation, 2007)
According to the crite1ia of reliability, cost-efficiency andenvironmental fiiendliness the traffic on inland waterways inthe Republic of Croatia has not been fully used. The study analyzesthe current condition of vessels on inland waterways in theRepublic of Croatia. Also, statistical method and methods ofanalysis and comparison were used to research the current andpre-war condition from the aspect of type and number of vessels,and their capacity and engine power. The trend of the developmentof vessels in the Republic of Croatia has been comparedin relation to the European countries with developed inlandnavigation. The cun·ent trend in the Republic of Croatia isthe stagnation of the number of self-propelled vessels, and thereduction in the number of vessels intended for the transport ofgoods, then the reduction of total capacity and the enginepower of all the vessels, as well as changes in the relation betweenthe pushing and towing technologies in favour of thepushing technologies, in compliance with the trends in theworld. The methods of compilation and comparison were usedto research the preconditions of improving the condition of vessels,in compliance with the status and development in thecountries of the Danube COITidor VII.